PENGARUH RANCANGAN SITUS, HARGA, KEPERCAYAAN DAN KEAMANAN TERHADAP PEMBELIAN PRODUK FASHION MELALUI ONLINE SHOPPING - Megawati Wijaya; Farida Jasfar (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The increasing use of Internet provides an emerging prospect for online retailers, especially on fashion product. Online retailers need to know factors that affecting customer to buy online, then they can further develop their marketing strategies to convert potential customer. The objective(s) of this research was to analyze the effect of website design,price, trust and security on purchase of product fashion through online shopping. This study used Multiple Regression Analysis. The method used is Simple Random Sampling. 130 samples is chosen randomly from lectures and students of Trisakti University, Jakarta. The results show that there is positive influence of website design, trust andsecurity on purchase of fashion product through online shopping, but there is no positive influence of price on purchase of fashion product through online shopping.Keywords : Website Design, Price, Trust, Security, Online Shopping